ANALISIS PERBANDINGAN METODE WEIGHTED PRODUCT (WP) DENGAN METODE TECHNIQUE FOR ORDER OF PREFERENCE BY SIMILARITY TO IDEAL SOLUTIONS (TOPSIS) PADA SISTEM PENDUKUNG KEPUTUSAN PENGANGKATAN GURU TETAP BERBASIS WEB - Talondo, Daniel (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
In order to improve the welfare of teachers at SMK 1 Barunawati Jakarta, every year the principal is assigned by the Foundation to select 2 teachers to be recommended as permanent teachers by the chairman of the Sekar Laut Pelni Foundation according to their competencies. The process of selecting permanent teachers is carried out by the principal with consideration from the deputy principals and head of administration. So far, the appointment of permanent Foundation teachers is still done manually without considering the characteristics of the assessment criteria. Based on these problems, this research aims to analyze the comparison of the Weight Product (WP) method and the Technique for Order of Preference by Similarity to Ideal Solutions (TOPSIS) method in the web-based Decision Support System for appointing permanent Foundation teachers. The Weighted Product (WP) method uses a multiplication technique to connect attribute ratings where the rating for each attribute must first be raised to the power of the weight of the attribute in question. Meanwhile, the TOPSIS method is based on the concept where the best selected alternative not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution. From this research, comparison results were obtained using Euclidean Distance after ranking values ​​in the Web-based SPK application, so that the WP method obtained a result accuracy of 99.93%, while the TOPSIS method had a result accuracy rate of 99.52% and at the black box and white box testing stage of the web-based decision support system, it was 100% goes well. The ranking results of both methods on the web-based system obtained the same ranking order so that this system can make it easier for school principals to recommend permanent teachers to the head of the Foundation.